Perlindungan Hukum bagi Korban Penipuan Berkedok Rekrutmen Kerja Secara Online - Nurmala Dewi; Aturkian Laia (INDO PUBLISHING, 2026)
This article examines the legal protection available to victims of online job-recruitment fraud in Indonesia, a phenomenon that has grown alongside the widespread use of social media and messaging applications as channels for disseminating fake job vacancies. Employing normative legal research through statutory, conceptual, and case-based approaches, the article analyzes the modus operandi of online recruitment fraud, the forms of preventive and repressive legal protection available to victims, the criminal liability of perpetrators, the roles of government and digital platforms, obstacles in law enforcement, and recommendations for regulatory reform. The findings indicate that Indonesia's legal framework comprising Law Number 1 of 2023 on the Criminal Code, Law Number 1 of 2024 on the Second Amendment to the Electronic Information and Transactions Law, Law Number 27 of 2022 on Personal Data Protection, and Law Number 8 of 1999 on Consumer Protection provides an adequate normative basis to prosecute perpetrators and protect victims' rights, yet its implementation remains fragmented, poorly integrated, and constrained by difficulties in digital evidence and cross-border enforcement. The article recommends strengthening inter-agency coordination, imposing layered verification obligations on job-vacancy platforms, and reinforcing victims' restitution rights within criminal proceedings.